A letter for Leo - Ruzzier, Sergio, 1966- (Clarion Books, Houghton Mifflin Harcourt, 2014)
When Leo, a weasel mailman, rescues a young bird that was separated from his flock, the two become friends and Leo's dream of one day receiving a letter of his own may finally come true.